Optimizing Smart Factories: A Data-Driven Approach (Global Journals of Research in Engineering, 2024)
Since the first industrial revolution the leading role of emerging technologies has been highlighted in modernizing the industry and developing the workforce This study explores the impact of Industry 4 0 digital technologies on manufacturing competitiveness focusing on Finnish SMEs within the EU with a sample n 123 It utilizes extensive 2022 European Manufacturing Survey EMS22 data Advanced statistical techniques reveal complex connections between automation competitive edge on services and innovation models among other factors Robust statistical methods including component and reliability analyses reinforced the findings The conclusion offers critical insights and identifies areas for further research in combining innovative manufacturing practices with technology education
Keywords: industry 40; competitiveness and employment; supply chain contracts; human resources; training and competence